THE RELATIONSHIP OF CUSTOMER EXPERIENCE, CUSTOMER ENGAGEMENT, CUSTOMER SATISFACTION, AND CUSTOMER LOYALTY IN SHOPEE E-COMMERCE - Liputri, Evelin; Gosal, Gladys (FEB Universitas Sam Ratulangi Manado, 2024)
Abstract. The current rapid pace of information technology has changed people's way of shopping. People no longer need to leave the house to buy various necessities. One of the most popular e-commerce in Indonesia is Shopee. This research aims to find out the effect of customer experience on customer engagement and satisfaction in order to increase customer loyalty in Shopee e-commerce. This research was conducted quantitatively by distributing questionnaires to 257 respondents. The sampling technique uses a purposive sampling method with the criteria of making a purchase at Shopee at least once a month and being over 17 years old. Research data were analyzed using Structural Equation Modeling-Partial Linear Squares (SEM-PLS). Of the five proposed hypotheses, four were accepted, while one, namely H3, asserting that 'involvement positively affects customer satisfaction,' was rejected. To achieve customer loyalty, companies must be able to provide satisfaction to their customers through involvement in interacting with the company and providing an impressive experience while using the company's services and products. Abstrak. Pesatnya perkembangan teknologi informasi saat ini telah mengubah cara masyarakat dalam berbelanja. Masyarakat tidak perlu lagi keluar rumah untuk membeli berbagai kebutuhan. Salah satu e-commerce terpopuler di Indonesia adalah Shopee. Penelitian ini bertujuan untuk mengetahui pengaruh pengalaman pelanggan terhadap keterlibatan dan kepuasan pelanggan guna meningkatkan loyalitas pelanggan pada e-commerce Shopee. Penelitian ini dilakukan secara kuantitatif dengan menyebarkan kuesioner kepada 257 responden. Teknik pengambilan sampel menggunakan metode purposive sampling dengan kriteria melakukan pembelian di Shopee minimal sebulan sekali dan berusia di atas 17 tahun. Data penelitian dianalisis menggunakan Structural Equation Modeling-Partial Linear Squares (SEM-PLS). Dari lima hipotesis yang diajukan, empat hipotesis diterima, sedangkan satu hipotesis yaitu H3 yang menyatakan bahwa 'keterlibatan berpengaruh positif terhadap kepuasan pelanggan' ditolak. Untuk mencapai loyalitas pelanggan, perusahaan harus mampu memberikan kepuasan kepada pelanggannya melalui keterlibatan dalam berinteraksi dengan perusahaan dan memberikan pengalaman yang mengesankan selama menggunakan jasa dan produk perusahaan.